Nursing care provided to a patient diagnosed with schizophrenia, using the International Classifi cation for Nursing Practice (ICNP®) - Pawłowski, Piotr; Markiewicz, Renata; Dobrowolska, Beata (Nursing in the 21st Century, 2022)
NURSING CARE PROVIDED TO A PATIENT DIAGNOSED WITH SCHIZOPHRENIA, USING THE INTERNATIONALCLASSIFICATION FOR NURSING PRACTICE (ICNP®)Introduction. Schizophrenia spectrum disorders are a major challenge for modern psychiatry. Epidemiological data indicate an increasing trend in the prevalence of such disorders, as well as other disorders from the schizophrenia spectrum. In a long-term perspective, this means that highly specialised (both nursing and medical) care, broadly understood community care, and innovative rehabilitation methods able to reduce cognitive and executive defi cits will be necessary.Aim. The aim of this paper is to propose the use of the International Classifi cation for Nursing Practice (ICNP®) in the process of diagnosing and planning care for patients with schizophrenia.Material and method. The paper is based on the individual case study method and for the analysis of the obtained data the following research techniques were used: interview, observation, measurement, documentation analysis. The research tools: Individual Nursing Care Card, Mental Health Assessment Card, SAD PERSONS Scale for Suicide Risk Assessment, Beck Depression Inventory (BDI), Global Assessment of Functioning (GAF), Hospital Anxiety and Depression Scale (HADS), and C-HOBIC Fatigue Assessment Scale.Results. The collected data allow the formulation of 15 diagnoses in accordance with ICNP®. For the three selected diagnoses, a nursing care plan was drawn up, which included, depending on the patient’s needs, nursing interventions.Conclusions. ICNP® as a classifi cation of nursing diagnoses allows the drafting of nursing diagnoses related to the mental state of